La migracion caboverdeana hacia la Argentina. Análisis de una alternativa - Maffia, Marta M. (Trabalhos de Antropologia e Etnologia, 2020)
This work studies the migration from Cabo Verde to Argentina as a possible alternative location within the referential cliagram. This stresses little, or no studied aspects of the following: the variable analyses- or regulating elements - on the «taking of decision», the different kinds of settling places and of their adaptation to the chosen country, in this case, Argentina.